Federalism in South Sudan—Options for Power Sharing in the Permanent Constitution - de Villiers, Bertus (Sage Publications, 2014)
© The Author(s) 2013.The young nation of South Sudan is currently engaged in a review of its Transitional Constitution with the aim of finalizing a Permanent Constitution by 2015. One of the key issues the subject of negotiations is whether the Permanent Constitution should contain power-sharing features and if so, whether those features should be formal or informal. While it is widely accepted that the Permanent Constitution will contain federal elements, this article gives consideration to the way in which formal and informal power-sharing arrangements that are found in federations such as Nigeria, South Africa and Ethiopia, could be employed by South Sudan.